A Book Review - Voices from the Classroom: Performing Case Study Action Research - Nicholas D. Hartlep (Networks: An Online Journal for Teacher Research, 2013)
Voices from the Classroom is about how to perform case study action research. The book is 130 pages in length, and contains ten chapters. Written sequentially, each chapter is related to sections of an action research study. For instance, how to introduce the study (chapter 2); how to write a literature review (chapter 3); how to describe the setting, sampling, and participants (chapter 4); how to collect data (chapter 5); how to confirm the trustworthiness of the study (chapter 6); how to analyze data (chapter 7); how to write up the results (chapter 8); and how to discuss implications of the study (chapter 9). Chapter 1 serves as an introduction of “teacher as researcher,” while the tenth chapter provides examples of two completed case study action research papers authored by Sargent’s students.